Perancangan Pisau Pemangkas Flashing Sebagai Upaya Mengurangi Cacat Produk Seal Washer (Studi Kasus: PT. XYZ) - Khannan, Muhammad Abdul; Saputra, Andri (Manutech : Jurnal Teknologi Manufaktur, 2025)
The relatively high number of gasket defects after the finishing process is one of the problems faced by PT. XYZ. The defect is located on the inside of the seal washer, which is not completely cut during the finishing process. The objective of this research is to design and manufacture a flashing trimming blade to reduce the number of defects of seal washer at PT. XYZ. The design stages of the trimmer blade include creating two- and three-dimensional drawings using AutoCAD version 2017, turning iron (blade material) using a CY-1760 lathe, and testing the success and efficiency of finishing seal washer without and with the use of a trimmer blade. The study results show that the trimming blade is capable of finishing the gasket with good performance. By using trimming blade in the finishing stage, the number of defects can be reduced from 359 pieces (20%) to 50 pieces (2.7%), and the finishing time can be reduced by 86% from 70 seconds to 5 seconds per product.